The Effects of Rural Electrification on Employment: New Evidence from South Africa - Dinkelman, Taryn (American Economic Review, 2011)
This paper estimates the impact of electrification on employment growth by analyzing South Africa's mass roll-out of electricity to rural households. Using several new data sources and two different identification strategies (an instrumental variables strategy and a fixed effects approach), I find that electrification significantly raises female employment within five years. This new infrastructure appears to increase hours of work for men and women, while reducing female wages and increasing male earnings. Several pieces of evidence suggest that household electrification raises employment by releasing women from home production and enabling microenterprises. Migration behavior may also be affected. (JEL H54, L94, L98, O15, O18, R23)